Management of Pre-cervical Uterine Torsion in a Salem Black Goat - Vinayaga, Senthil Kumar Jawahar; Ruthrakumar, Ravichandran; Angusamy , Suganya (The Indian Journal of Animal Reproduction, 2025)
Successful management of pre-cervical uterine torsion in a Salem Black goat by caesarean section was reported.